Republic of Tajikistan : 2011 Article IV Consultation, Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance for Performance Criteria and Modification of Performance Criterion-Staff Report; Staff Supplements; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Tajikistan's economic performance has been satisfactory, but challenges still remain. Executive Directors agreed that the challenge is to support recovery while addressing risks to macroeconomic stability. They emphasized for prudent monetary stance to avoid inflation and also to address vulnerabilities in the financial sector. Directors agreed that structural reforms should be given top priority. They welcomed progress in establishing a framework for agricultural financing. Directors commended plans to improve the business climate through a reform of the tax regime and improved transparency and accountability of state-owned enterprises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet